MANDIBULAR INCISOR EXTRACTION: A 5-YEAR FOLLOW-UP - BEYCAN, KADİR (ISTANBUL UNIV, FAC DENTISTRY, 2016)
This case report presents the mandibular incisor extraction treatment of a patient with dental Class I malocclusion and lower crowding, in whom one mandibular incisor extraction was selected as the treatment of choice to improve the dental occlusion. A 19-year-old male patient's chief complaint was the crowding of lower incisors. He had a straight profile with normal upper and lower lip projection. Upper and lower dental midlines were coincident with the facial midline. The patient had Class I molar and canine relationships on both sides. He had Class I skeletal relationship, low angle vertical pattern, and proclined upper and lower incisors. The treatment plan included the extraction of lower right central incisor to resolve the crowding. At the end of 16-month active fixed treatment, lower dental crowding was resolved. At the 5-year follow-up, the patient had a stable occlusion, with the results of the orthodontic treatment maintained.
Keywords: Mandibular incisor; crowding, extraction; occlusion; long term follow-up